2020
DOI: 10.1001/jamainternmed.2020.3271
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Psychological Distress—Changes in Internet Searches for Mental Health Issues in New York During the Pandemic

Abstract: The highly contagious nature of severe acute respiratory syndrome coronavirus 2, leading to the coronavirus disease 2019 (COVID-19) pandemic, necessitated the enactment of public health actions on an unprecedented scale in US history. Closure of all nonessential businesses along with strict socialdistancing measures were instituted to curb disease transmission across the nation. After gradually closing some businesses and schools, the state of New York instituted New York State on PAUSE, a statewide lockdown, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
2
18
1
1
Order By: Relevance
“…This is in line with other Italian studies during the COVID-19 outbreak [28, 29, 31], and also with previous studies highlighting that older adults present greater self-control, emotional self-regulation, and better-coping strategies compared to younger adults [32,33]. A further potential explanation is that younger people might experience higher stress levels because they increased the use of the Internet and social media during the lockdown period [34][35][36].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with other Italian studies during the COVID-19 outbreak [28, 29, 31], and also with previous studies highlighting that older adults present greater self-control, emotional self-regulation, and better-coping strategies compared to younger adults [32,33]. A further potential explanation is that younger people might experience higher stress levels because they increased the use of the Internet and social media during the lockdown period [34][35][36].…”
Section: Discussionsupporting
confidence: 91%
“…The identified themes provide insights into why a relatively high number of people with cancer are reporting clinically meaningful levels of stress and anxiety during the pandemic [12,13,17,18]. In fact, the number of internet searches for anxiety, panic attack, and insomnia significantly increased in the New York area during the COVID-19 lockdown which suggests an overall surge in these symptoms in the general population [28]. More specifically, in a study of oncology patients during COVID-19 [17], a high percentage of patients reported stress levels that were consistent with posttraumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoringansätze wie die COSMO-Studie, die nach Angst direkt fragt und wöchentliche Ergebnisse vorlegt, kommt zu einem ähnlichen Bild [22]. Neuere Datenanalysen, die auf Social Media und Suchmaschinen-Abfragen basieren, bestätigen diese rückläufigen Trends ebenfalls [23,24]. Als weniger wahrscheinliche, aber alternative Erklärung kommen auch Copingund Adaptationseffekte infrage.…”
Section: Gute Studien Sind Rarunclassified